Introducing Lean Canvas: an Assistance for SMKN 3 Tuban Students in Composing Business Plan - Niswatin Nurul Hidayati; Diki Ahmad Mudhakir; Moch. Saifullah (Universitas Nurul Jadid, 2023)
Lean Canvas is a framework that aids in designing a focused and efficient business model, highly suited to the rapidly changing business environment of today. Lean Canvas is a framework or tool used for rapidly and efficiently designing and developing business models. The objective of this assistance was to introduce Lean Canvas model for SMKN 3 Tuban students in order to be able to use it for composing business plan. Community service in the form of mentoring for students at SMKN 3 Tuban was conducted with a total of 5 meetings within 1 month. Before receiving guidance on creating a business plan matrix using Lean Canvas, the students received related materials on entrepreneurship, an introduction to business plans, marketing, human resources, creative economy, product development, e-commerce, and finance. There were 20 participating students in the mentoring program. Out of these 20 students, there were 5 students grouped together, each group having one product which consisted of banana chips in various flavors. Additionally, there was 1 student who had a fruit salad business